TINGKAT KEPUASAN WISATAWAN TERHADAP WISATA KULINER DI KABUPATEN BADUNG - I Wayan Mertha; Novanti Murni Prasetyawati (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2017)
This study aims to determine the level of customer satisfaction of culinary tourism in Kedonganan Beach. Tourists assess the products and services of existing cafes with five dimensions of service quality, namely: tangibles, reliability, responseiveness, assurance and empathy. The number of indicators from all five dimensions is 23 indicators. There are as many as 24 cafes in Kedonganan area, and selected only six cafes representing the north, center, and south of the area. At the six cafes are distributed 100 questionnaires for one week to the guests who have finished enjoying dinner. Collected data were analyzed using ServQual method and Importance Performance Analysis (IPA). The result of the research shows that overall tourists feel that they are not satisfied with Kedonganan Beach culinary, because the difference between expectation and their perception on the 23 indicators is still negative (- 0.74). While the analysis is done by IPA method, it is known that there are four indicators that are considered very important to do, but the implementation is still not in accordance with expectations. The four indicators include food menu and presentation. Indicators assessed to exceed the expectations of tourists include the completeness of the facility, understanding the needs of guests, and speed of service. In addition there are nine indicators that hope and implementation is appropriate, so it needs to be maintained by the management of all cafes in Kedonganan. The nine indicators include food taste, price, and service.